PENERAPAN PENDEKATAN BEHAVIORISTIK DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL ALQURAN SANTRI - MUTTAQIN, MUTTAQIN (AflahConsilia : Jurnal Bimbingan dan Konseling, 2024)
Application of the Behavioristik approach is the theory that his discussion is about patterns of human behavior which in this case is to memorize the qur'an, which is one of the most glorious worship activities run by a Muslim, from all walks of life be it male or female adults or even children, in this study the researchers raised the research Application form fokos Approach Behavioristik in improving the ability of Memorizing the Quran Naat in the hut Qur'anic Tahfidh boarding school children An "Nafi'iyah" Tulangan of Sidoarjo.Researchers using this type of qualitative research approach to fieldwork data collection techniques, using observation, interview and documentation. While the data analysis techniques using domain analysis technique of measures the reduction of data, display data, and verification. Test the validity of the data is done through perseverance observer, triangulation, membercheck and external audit.The results of this research is the application of Behavioristik Approach in improving the ability of Memorizing the Koran Students in boarding schools of children Tahfidz An-Nafi'iyah Tulangan Sidoarjo realized in several stages, namely: a) planning stages, b) Stage of implementation, c) stages of the evaluation.